Policies for Developing Foreign Exchange Markets; Occ. Paper No. 60. (Occasional Papers; Occasional Paper ;, 1988)
This paper describes and analyzes forward market systems with varying degrees of sophistication, and it assesses them from the viewpoint of a smaller industrial or developing country asking itself how it could institute such a system, or how it could further develop an existing system in a way consistent with its institutional and macroeconomic structure. All industrial countries except Iceland now have forward exchange markets in which the rate is determined by the market. Forward markets that have been liberalized in several countries in the 1980s have matured quickly. There are several variants of market-determined systems which could be envisaged. An auction market could be devised for forward transactions, but is unlikely to be practical, because the supply of forward exchange probably may not be determined in advance sufficiently accurately. As the last stage of its development, the market could be extended from underlying commercial transactions to forward transactions of a purely financial character, a process that is taking place in most of the few industrial countries that have retained regulated forward systems. Development of a forward market is not a panacea for incorrect financial policies. In fact, cultivation of the market will require the adoption and maintenance of realistic financial policies.